Perspectives on etonogestrel implant use in HIV-infected women in Cape Town, South Africa: a qualitative study among providers and stakeholders - Brown, Anna (Adolescent Health Research Institute, 2019)
Access to a range of safe and effective modern contraceptive methods enables women to make free and informed choices about their reproductive lives and broadly improves maternal and child health outcomes. Successful avoidance of unintended pregnancy and the corresponding ability to plan for pregnancy are especially valuable in the context of Human Immunodeficiency Virus (HIV) infection. Revised South African national guidelines seeking to expand overall contraceptive access were released in 2012 and, in response to the severity of the domestic HIV epidemic, specifically detailed the sexual and reproductive health rights and needs of HIV-positive women. Six years later, evaluation of the implementation and impact of these guidelines, as well as of more recent policy responses in this area, is necessary. This need for evaluation is outlined in Part A of this mini-dissertation in the form of a research proposal. A literature review (Part B) assesses what is currently known about considerations surrounding contraceptive decision-making in the context of HIV and antiretroviral therapy (ART). The use of the subdermal Long Acting Reversible Contraceptive (LARC) implant in HIV-positive women is explored in depth, given that the 2012 guidelines introduced the method as an entirely new option for South African women, as well as in light of recent controversy surrounding the implant’s provision to women taking the first-line ART drug, efavirenz (EFV). A journal-style article structured for submission to BMC Public Health (Part C) then uses thematic qualitative methodology to explore primary family planning provider and other relevant stakeholder perspectives on the provision of implants to HIV-positive women clients attending Cape Town primary care facilities. The study adds to existing literature regarding implant provision in the context of HIV and ART, and offers new insight into the impact of a 2014 South African Department of Health decision to recommend against the then-newly introduced implant as an option for women taking EFV-based ART. This research finds that several converging factors may have lead primary providers to view the implant as broadly contraindicated in all HIV-positive clients regardless of their iii exposure to EFV, namely: insufficient provider training; provider and community unfamiliarity with and scepticism about the new method; structural pressures on providers to keep up to date with and provide wide-ranging integrated services in busy clinical environments; and inadequate stakeholder consultation surrounding the wording and overall appropriateness of the implant/EFV guidance itself. Recommendations are provided in the article, including the need for: the retraining of primary healthcare providers in rights and choice-based family planning (particularly in implant provision and counselling); simplified counselling messages and user-friendly decision-making tools to help providers facilitate informed contraceptive choice for HIV-positive women; generalized beneficiary and community sensitization/education about implants including in the context of HIV and ART; and more comprehensive stakeholder/beneficiary consultation in future contraceptive policy-related endeavors.